Perancangan Aplikasi Pencarian File Teks dengan Menggunakan Algoritma Colussi Dan Algoritma Simon - Sastra Ramadanu (JURIKOM (Jurnal Riset Komputer), 2019)
String matching is a string processing which is the main requirement in obtaining information in the text that helps humans find information faster because it has an algorithm for searching the string. Search algorithms have advantages and disadvantages in search, matching, speed, accuracy, and others. By performing a performance comparison analysis, it can be seen the speed and accuracy in the search process time and word matching and the percentage of memory used in one process of each of these algorithms. The colussi algorithm is a search that has been specifically determined by the system or algorithm where the colussi algorithm is an improvement of the boyer moore algorithm which is a right-to-left search while simon algorithm is a classic algorithm that is widely known as a method that can identify local similarities ) that is the process of making two nucleotide local sequences or protein sequences where similarities between the two sequences will be seen.